2006
DOI: 10.1002/j.1556-6678.2006.tb00434.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Adult Attachment Style in Forgiveness Following an Interpersonal Offense

Abstract: The role of attachment style in relation to forgiveness was investigated in 2 betrayal interviews. Blood pressure and heart rate were assessed, along with attachment style, forgiveness, empathy, and emotional expressiveness. Securely attached individuals were more forgiving of the specific offense, had higher levels of trait forgiveness, and expressed more positive emotion. Securely attached adults had lower interview systolic blood pressure and exhibited greater blood pressure recovery. Attachment style may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0
8

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 65 publications
4
57
0
8
Order By: Relevance
“…Como resultado de ello, sería esperable que las personas con mayor seguridad en el apego manejaran mejor la amenaza representada por una transgresión y, por lo tanto, estuviesen más inclinadas a perdonar. Al respecto, existe una serie de estudios que han sido consistentes en confirmar la relación entre ambas variables, tanto si el perdón es concebido como un estado (e.g., Davidson, 2000;Lawler-Row et al, 2006) o como un rasgo (e.g., Webb et al, 2006).…”
Section: Apego Y Perdónunclassified
See 2 more Smart Citations
“…Como resultado de ello, sería esperable que las personas con mayor seguridad en el apego manejaran mejor la amenaza representada por una transgresión y, por lo tanto, estuviesen más inclinadas a perdonar. Al respecto, existe una serie de estudios que han sido consistentes en confirmar la relación entre ambas variables, tanto si el perdón es concebido como un estado (e.g., Davidson, 2000;Lawler-Row et al, 2006) o como un rasgo (e.g., Webb et al, 2006).…”
Section: Apego Y Perdónunclassified
“…La teoría del apego (TA), que es un marco conceptual que permite comprender diversos aspectos del funcionamiento en relaciones cercanas, se ha incorporado al estudio del perdón (e.g., Gassin y Lengel, 2011;Kachadourian, Fincham y Davila, 2004;Lawler-Row, Younger, Piferi y Jones, 2006;Webb, Call, Chickering, Colburn y Heisler, 2006).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Individual differences in the need to belong, thus, bear some resemblance to insecure attachment (perhaps especially the preoccupied attachment style), which in turn has been shown to be negatively associated with both state and trait forgiveness (Brown & Phillips, 2005;Burnette, Taylor, Worthington, & Forsyth, 2007;Kachadourian, Fincham, & Davila, 2004;Lawler-Row, Younger, Piferi, & Jones, 2006;Webb, Call, Chickering, Colburn, & Heisler, 2006). Furthermore, Leary et al (2008) report that the NTBS correlates with measures of neuroticism, fear of rejection, and manifestations of borderline personality disorder in normal persons, all of which have conceptual links with insecure attachment and one of which (neuroticism) has been shown to be negatively associated with measures of forgiveness (Brown, 2003;McCullough, Bellah, Kilpatrick, & Johnson, 2001).…”
Section: Forgiveness and The Need To Belongmentioning
confidence: 99%
“…Attachment security has been found to correlate with increased situational forgiveness and trait forgiveness (e.g., Burnette, Taylor, Worthington, & Forsyth, 2007;Kachadourian, Fincham, & Dvila, 2005, Lawler-Row, Younger, Piferi, & Jones, 2006. Hall, Fujikawa, Harcrow, Hill, and Delaney (2009) found that unforgiving was positively correlated with both avoidant God attachment and anxious God attachment suggesting a link between forgiveness, attachment and relational spirituality.…”
Section: Introductionmentioning
confidence: 99%